Agami (The Time Ahead, 1984), the First "Short Film" of Bangladesh: Toward a New Cinematic Aesthetic of Imaging Time and Nation. (June 2019) - Akhter, Fahmida
Morshedul Islam's Agami ( The Time Ahead, 1984), focusing on the theme of the Liberation War of Bangladesh, is Bangladesh's first "short film" or independent film, made outside the domain of commercial film production. The film pioneers in investing the memory of the Liberation War with allegorical potential in order to interpret the socio-political condition of Bangladesh under the military dictatorship of Lieutenant General Hussain Muhammad Ershad. His regime lasted for eight years, from 1982 to 1990. Linear progression of time is interrupted in this film by a constant collapsing of the past, present, and future into each other through the treatment of storytelling, flashbacks, and flashforward. This disruption of time's flow, I will argue, is employed to serve a nationalistic purpose, offering an insight into the psychic condition of contemporary Bangladesh and its socio-political crisis under the military dictatorship of General Ershad. In analyzing the film, my main concern is to understand how a film like Agami, with its oppositional socialist commitments and with the aspiration of creating an alternative mode of cinematic language, constructs the ideas of gender, nation, and memory during a period of pronounced political turmoil. I will also explore its new cinematic aesthetics as a "short film" or independent film of Bangladesh.